Tahlil al-Akhtha’ al-Shautiyyah li al-Kalimat al-Thayyibat fi Hayat al-Muslimin (Dirasah Tahliliyyah Shautiyyah) - Misbahul Munir (Arabic Education Program IAIN Pekalongan, 2018)
This research aims to explain the sound error al-kalimÄh aá¹-á¹ayyibah, vowels and consonants. The research conducted at UIN Yogyakarta. Sources of data obtained from Arabic Linguistic Studies of Post Graduate Students in UIN Yogyakarta. The method used is descriptive-qualitative with case study approach. Data collection of this research used interviewing, taking notes, and recordings. This research shows that the mistakes found in vowels; either short, long, and double vowel sound. Fatá¸¥ah(ÙŽ) sounds /a/ becomes /o./ á¸Œammah(Ù) sounds /u/ becomes /o/, /Å«/, dan sukÅ«n/Ù’./ Kasrah(Ù) sounds /i/ becomes /e./ Syaddah(Ù‘) which read double will be not double. Fatá¸¥ah(ÙŽ) which followed alif(Ø§), it sounds /Ä/ and becomes /a./ Fatá¸¥ah(ÙŽ) which followed alif(Ø§) dan tilda( ) above it, it sounds /Ä/ and becomes /a./ Fatá¸¥ah(ÙŽ) which followed wawu sukÅ«n(ÙˆÙ’), sounds /au/ and becomes /ao./ Fatá¸¥ah(ÙŽ) which followed yaâ€™ sukÅ«n(ÙŠÙ’), sounds /ai/ and becomes /ei./ The error sound of the consonants, consonant phoneme sound Ø¹/â€˜/ becomes Ø§/â€™/, Ø/á¸¥/ becomes Ù‡/h/ and Ùƒ/k/, Ø¸/áº“/ becomes Ø²/z/ and Ø¬/j/, Ø´/sy/ becomes Ø³/s/, Ù‚/q/ becomes Ùƒ/k/, Ø°/Å¼/ becomes Ø¸/áº“/ and Ø¯/d/, Øª/t/ becomes Ø·/á¹./ The sound of the vowels and consonants errors occur due to there is link between language with speakers.